ANALISIS PENYUSUNAN ANGGARAN PADA KANTOR KELURAHAN KARAME KECAMATAN SINGKIL KOTA MANADO TAHUN ANGGARAN 2014 - Kaumbang, Judisty; Pangemanan, Sifrid S.; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The budget is estimated to be achieved over a certain period set forth in the financial measures. Stage Budgeting is the first stage of the budgeting process. At this stage, usually by the executive budget plan that will implement the budget. The purpose of this study was to determine the budget formulation process at the Village Office KarameSingkil District of Manado City budget year 2014. The method used is descriptive and data obtained through field studies. The results were obtained at the Village Office KarameSingkil District of Manado City has implemented the budget process in accordance with Regulation No.27 of 2013 on guidelines for the budgeting of fiscal year 2014. At the Village Office KarameSingkil District of Manado City budget formulation for 2014 was in accordance with Regulation No. 27, 2013. the preparation of the budget at the Village Office KarameSingkil District of Manado City has been presented in the form of local budget cycle. Keywords: analysis, making, budget